Serotonin transporter availability in physically aggressive personality disordered patients: associations with trait and state aggression, and response to fluoxetine - Daniel R. Rosell; Mark Slifstein; Judy Thompson; Xiaoyan Xu; M. Mercedes Perez-Rodriguez; Margaret M. McClure; Erin A. Hazlett; Antonia S. New; Nabeel Nabulsi; Yiyun Huang; Richard E. Carson; Larry S. Siever; et al. (Psychopharmacology, 2023)

Amphetamine-induced striatal dopamine release in schizotypal personality disorder - Judy L. Thompson; Daniel R. Rosell; Mark Slifstein; Xiaoyan Xu; Ethan G. Rothstein; Yosefa A. Modiano; Lawrence S. Kegeles; Harold W. Koenigsberg; Antonia S. New; Erin A. Hazlett; Margaret M. McClure; M. Mercedes Perez-Rodriguez; et al. (Psychopharmacology, 2020)

Binding of the D3-preferring antipsychotic candidate F17464 to dopamine D3 and D2 receptors: a PET study in healthy subjects with [11C]-(+)-PHNO - Mark Slifstein; Anissa Abi-Dargham; Ragy R Girgis; Raymond F Suckow; Thomas B Cooper; Chaitanya R Divgi; Pierre Sokoloff; Ludovic Leriche; Patrick Carberry; Shunichi Oya; Simon K Joseph; Marlène Guiraud; et al. (Psychopharmacology, 2020)

Preferential binding to dopamine D3 over D2 receptors by cariprazine in patients with schizophrenia using PET with the D3/D2 receptor ligand [11C]-(+)-PHNO - Ragy R. Girgis; Mark Slifstein; Deepak D’Souza; Yih Lee; Antonia Periclou; Parviz Ghahramani; István Laszlovszky; Suresh Durgam; Nika Adham; Nabeel Nabulsi; Yiyun Huang; Richard E. Carson; et al. (Psychopharmacology, 2016)
Rationale Second-generation antipsychotics occupy dopamine D 2 receptors and act as antagonists or partial agonists at these receptors. While these drugs alleviate positive symptoms in patients with schizophrenia, they are less effective for treating cognitive deficits and negative symptoms. Dopamine D 3 receptors are highly expressed in areas of the brain thought to play a role in the regulation of motivation and reward-related behavior. Consequently, the dopamine D 3 receptor has become a target for treating negative symptoms in combination with D 2 antagonism to treat positive symptoms in patients with schizophrenia. Objective The purpose of this study was to determine the cariprazine receptor occupancies in brain for D 2 and D 3 receptors in patients with schizophrenia. Methods Using [ 11 C]-(+)-PHNO as a radioligand, positron emission tomography (PET) scans were performed in eight patients at baseline and postdose on days 1, 4, and 15. Plasma and cerebrospinal fluid (CSF) samples were analyzed for cariprazine concentrations. Results A monotonic dose-occupancy relationship was observed for both receptor types. After 2 weeks of treatment, near complete (∼100 %) occupancies were observed for both receptors at a dose of 12 mg/day. At the lowest cariprazine dose (1 mg/day), mean D 3 and D 2 receptor occupancies were 76 and 45 %, respectively, suggesting selectivity for D 3 over D 2 receptors at low doses. An exposure-response analysis found a ∼3-fold difference in EC 50 (D 3 = 3.84 nM and D 2 = 13.03 nM) in plasma after 2 weeks of dosing. Conclusion This PET imaging study in patients with schizophrenia demonstrated that cariprazine is a D 3 -preferring dual D 3 /D 2 receptor partial agonist.

Prefrontal dopamine D1 receptors and working memory in schizotypal personality disorder: a PET study with [11C]NNC112 - Judy L. Thompson; Daniel R. Rosell; Mark Slifstein; Ragy R. Girgis; Xiaoyan Xu; Yosefa Ehrlich; Lawrence S. Kegeles; Erin A. Hazlett; Anissa Abi-Dargham; Larry J. Siever (Psychopharmacology, 2014)

In vivo binding of the dopamine-1 receptor PET tracers [11C]NNC112 and [11C]SCH23390: a comparison study in individuals with schizophrenia - Eline M. P. Poels; Ragy R. Girgis; Judy L. Thompson; Mark Slifstein; Anissa Abi-Dargham (Psychopharmacology, 2013)

Imaging human reward processing with positron emission tomography and functional magnetic resonance imaging - Nina B. L. Urban; Mark Slifstein; Shashwath Meda; Xiaoyan Xu; Rawad Ayoub; Olga Medina; Godfrey D. Pearlson; John H. Krystal; Anissa Abi-Dargham (Psychopharmacology, 2012)

Serotonin 1A receptor availability in patients with schizophrenia and schizo-affective disorder: a positron emission tomography imaging study with [11C]WAY 100635 - W. Gordon Frankle; Ilise Lombardo; Lawrence S. Kegeles; Mark Slifstein; John H. Martin; Yiyun Huang; Dah-Ren Hwang; Elisa Reich; Claudine Cangiano; Roberto Gil; Marc Laruelle; Anissa Abi-Dargham (Psychopharmacology, 2006)

In vivo affinity of [18F]fallypride for striatal and extrastriatal dopamine D2 receptors in nonhuman primates - Mark Slifstein; Dah-Ren Hwang; Yiyun Huang; NingNing Guo; Yasuhiko Sudo; Raj Narendran; Peter Talbot; Marc Laruelle (Psychopharmacology, 2004)

Occupancy of brain serotonin transporters during treatment with paroxetine in patients with social phobia: a positron emission tomography study with [ 11 C]McN 5652 - Justine Kent; Jeremy Coplan; Ilise Lombardo; Dah-Ren Hwang; Yiyun Huang; Osama Mawlawi; Ronald Van Heertum; Mark Slifstein; Anissa Abi-Dargham; Jack Gorman; Marc Laruelle (Psychopharmacology, 2002)